Biology - Raven, Peter H.; Johnson, George B.; Losos, Jonathan B.; Singer, Susan R. (McGraw-Hill, 2005)
Contents: the origin of living things; biology of the cell; genetic and molecular biology; evilution; diversity of life on Earth; plant form and function; animal form and function; ecology and behavior.